Self-confidence pada remaja: Adakah peran fear of negative evaluation? - Vitaloka Eka Putri Suwandi; Dyan Evita Santi; Aliffia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract This study was conducted to determine the relationship between fear of negative evaluation and self-confidence in adolescents who are members of the IPPNU organization in Surabaya. The research used is quantitative by using correlational techniques. There were 67 subjects in this study. The sampling technique was purposive random sampling. The data collection method in this study was carried out by distributing questionnaires via the Google form using a Likert scale. The data analysis technique used is product moment analysis. The results obtained in this study showed which means there is no relationship between fear of negative evaluation and self-confidence in adolescents. This means that the lower the fear of negative evaluation by peers, the lower the self-confidence Keywords: Fear of negative evaluation, Self Confidence, adolescents